2021
DOI: 10.3390/ani11010140
|View full text |Cite
|
Sign up to set email alerts
|

Mate Choice in Double-Breeding Female Great Tits (Parus Major): Good Males or Compatible Males

Abstract: Producing two broods within the same season may be a good strategy by which short-lived species can maximize reproductive success. To produce two clutches in the same breeding season and to ensure offspring quality, choosing a good mate is important for females. Previous studies on double breeding focused on the associated influencing factors, and few studies examined how females choose social mates. Good genes and genetic compatibility are the two main hypotheses of the genetic benefit that females obtain fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…The identification of these valuable individuals is crucial for genetic management because they could constitute the breeder group for conservation and maximize reproductive success in captivity. It has been shown that individuals with higher heterozygosity, in relation to those of the same sex, have greater fitness (Brown, 1997; Garcia-Navas et al, 2009) and that females use diverse strategies when selecting males (good genes, genetic compatibility, and lower relatedness) which could increase offspring genetic diversity and reduce deleterious recessive allele expression (Zajitschek et al, 2009; Cutrera et al, 2012; Pilakouta & Smiseth, 2017; Fan et al, 2021), important aspects for successful captive breeding conditions. In this context, our simulation suggested that the genetic diversity of F1 populations is increased.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of these valuable individuals is crucial for genetic management because they could constitute the breeder group for conservation and maximize reproductive success in captivity. It has been shown that individuals with higher heterozygosity, in relation to those of the same sex, have greater fitness (Brown, 1997; Garcia-Navas et al, 2009) and that females use diverse strategies when selecting males (good genes, genetic compatibility, and lower relatedness) which could increase offspring genetic diversity and reduce deleterious recessive allele expression (Zajitschek et al, 2009; Cutrera et al, 2012; Pilakouta & Smiseth, 2017; Fan et al, 2021), important aspects for successful captive breeding conditions. In this context, our simulation suggested that the genetic diversity of F1 populations is increased.…”
Section: Discussionmentioning
confidence: 99%
“…We visited the nest boxes every 3 days after mid‐March to monitor the reproductive activities and clutch sizes of these two species (Fan et al., 2021 ). We recorded the first egg‐laying date, incubation date, and hatching date of the tits and flycatchers.…”
Section: Methodsmentioning
confidence: 99%
“…From mid‐May to early June, adults of tits and flycatchers breeding in artificial nest boxes were captured using the baffle method after the nestlings had hatched (Fan et al., 2021 ). The adults were placed in a cage (18 × 12 × 8 cm) lined with sterile craft paper by an experimenter wearing sterile latex gloves.…”
Section: Methodsmentioning
confidence: 99%
“…The Zuojia Nature Reserve (hereafter ZJ, 44 ο 1ʹ–45 ο 0ʹ N, 126 ο 0ʹ–126 ο 8ʹ E) is located in Jilin, Northeast China. The study site is located in the hill region of the Changbai Mountains and transitions to plains with an altitude of 200–530 m ( Fan et al 2021 ). The forest here is mainly consists of secondary growth deciduous woodland and the climate is temperate and subject to the eastern monsoon climate ( E et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%